2015
DOI: 10.1097/mcg.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Monopolar Soft-mode Coagulation Versus Heater Probe Thermocoagulation for Peptic Ulcer Bleeding

Abstract: For patients with gastroduodenal ulcer bleeding, soft coagulation using monopolar hemostatic forceps is more effective than heater probe thermocoagulation for achieving hemostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
0
22
0
5
Order By: Relevance
“…25,42 When compared with monopolar soft-coagulation forceps, the hydrothermal probe was less efficacious in primary hemostasis (96% vs 67%) as well as in rebleeding rate, with one perforation occurring in the heater probe group. 44 Injection and Cautery Methods for Bleeding Control …”
Section: Heater Probementioning
confidence: 99%
“…25,42 When compared with monopolar soft-coagulation forceps, the hydrothermal probe was less efficacious in primary hemostasis (96% vs 67%) as well as in rebleeding rate, with one perforation occurring in the heater probe group. 44 Injection and Cautery Methods for Bleeding Control …”
Section: Heater Probementioning
confidence: 99%
“…13 There have been several randomized controlled trials (RCTs) showing the usefulness of soft coagulation in the upper GI tract. [13][14][15] However, to our knowledge, there have been no studies on the benefits of soft coagulation for acute lower GI bleeding after subtotal colectomy. However, Fahrtash-Bahin et al reported that soft coagulation was an efficient technique for achieving hemostasis of intraprocedural bleeding during the endoscopic resection of large colonic lesions.…”
Section: Casementioning
confidence: 99%
“…La coagulation monopolaire, dont l'utilisation est dérivée de la dissection sousmuqueuse, a récemment montré son intérêt dans plusieurs études. Elle serait même plus efficace que la coagulation bipolaire dans les hémorragies ulcéreuses et à l'origine de moins d'effets indésirables [14].…”
Section: Pendant L'endoscopieunclassified